ANALISIS BIAYA TERAPI ASPIRIN DAN CLOPIDOGREL PADA PASIEN STROKE ISKEMIK DI RUMAH SAKIT ROYAL PRIMA TAHUN 2022 – 2025 - Nursaima Putri Nasution; Daimah Wirdatus Sanaun Harahap; Astriani Natalia Br Ginting (Jurnal Buana Farma, 2026)
Ischemic stroke is one of the leading causes of mortality and long-term disability, imposing a substantial economic burden due to high treatment and rehabilitation costs. Antiplatelet therapies such as aspirin and clopidogrel are commonly used for secondary prevention to reduce the risk of recurrent stroke; however, differences in treatment costs require evaluation to support efficient use of healthcare resources. This study aimed to analyze and compare the total cost and cost-effectiveness of aspirin and clopidogrel therapy in patients with ischemic stroke at Royal Prima General Hospital during the period 2022-2025. This study was an observational analytic study with a retrospective design using patients’ medical record data. The analysis was conducted from the hospital perspective by calculating direct medical costs, including drug costs, hospitalization, diagnostic examinations, and medical procedures. Pharmacoeconomic evaluation was performed using the Cost-Effectiveness Analysis (CEA) approach, with cost-effectiveness assessed through the calculation of the Cost-Effectiveness Ratio (CER) based on patients’ clinical outcomes. The results demonstrated differences in total treatment costs between aspirin and clopidogrel therapy, influenced by variations in cost components and patients’ clinical characteristics. In conclusion, cost-effectiveness analysis using CEA and CER can provide a scientific basis for selecting antiplatelet therapy that is rational and cost-efficient in the management of patients with ischemic stroke.